Identification of Challenging Diagnostic Factors in Livedoid Vasculopathy: A Retrospective Study - Qi F; Gao Y; Jin H (Dove Medical Press, 2024)
Fei Qi,1- 3 Yimeng Gao,1- 3 Hongzhong Jin1- 3 1Department of Dermatology, Peking Union Medical College Hospital, Chinese Academy of Medical Science and Peking Union Medical College, Beijing, People's Republic of China; 2State Key Laboratory of Complex Severe and Rare Diseases, Beijing, People's Republic of China; 3National Clinical Research Center for Dermatologic and Immunologic Diseases, Beijing, People's Republic of ChinaCorrespondence: Hongzhong Jin, Peking Union Medical College Hospital (Dongdan Campus), No. 1 Shuaifuyuan Wangfujing Dongcheng District, Beijing, 100730, People's Republic of China, Tel +86 10 6915 1500, Email jinhongzhong@263.netBackground: Livedoid vasculopathy is an uncommon cutaneous ulcerative dermatosis that is challenging to diagnose. Diagnostic delay brought both pain and uncurable atrophied scar to patients.Purpose: We conducted this study to identify the factors responsible for the initial misdiagnosis of livedoid vasculopathy and to identify possible methods to increase the diagnostic accuracy of livedoid vasculopathy.Patients and Methods: We conducted a retrospective medical record review to confirm the diagnosis of livedoid vasculopathy in patients who visited the Department of Peking Union Medical College Hospital for the first time. We used the Diagnosis Error Evaluation and Research taxonomy to evaluate missed cases.Results: Twenty-three patients (85.18%) had an alternate diagnosis, including 10 (43.4%) with two or more diagnoses. The average time from disease onset to the final diagnosis of livedoid vasculopathy was 4.61 ± 0.69 years. The major diagnostic errors were clinician assessment failures and failures in the timely follow-up and rechecking of patients. Allergic vasculitis was the most common misdiagnosis. Other alternate diagnoses include Henoch-Schoenlein purpura, pigmented purpuric dermatosis, eczema, erythema nodosum, and reactive perforating collagenases. Twenty-three patients (65.21%) received systemic corticosteroid therapy before the final diagnosis of livedoid vasculopathy.Conclusion: It is critical to raise the awareness of clinicians about livedoid vasculopathy, especially when patient present with extensive livedo racemosa or long-lasting purpuric lesions on the lower limbs. Long-term follow-up is necessary, especially for younger patients. Skin biopsy is recommended before systematic therapy.Keywords: livedoid vasculopathy, atrophie blanche, diagnostic accuracy, vasculitis